Pengaruh Literasi Keuangan, Gaya Hidup Terhadap Pengendalian Keuangan Generasi Milenial dengan Mediasi Self Control - Kristin Yolanda; Menik Indrati (Universitas Sains dan Teknologi Komputer, 2026)
This study examines to analyze the influence of financial literacy and lifestyle on the financial control of the millennial generation, with self-control as a mediating variable. This study is based on the phenomenon of low financial literacy and consumptive lifestyle patterns among millennials, which impact weak personal financial control. Data were obtained from 80 respondents in West Jakarta, specifically Kedoya, through an online questionnaire. The method used was quantitative with purposive sampling and data analysis using Partial Least Squares (PLS), a Structural Equation Modeling (SEM) model. The results show that financial literacy does not directly affect financial control, but has a significant effect on self control, which ultimately affects financial control indirectly. Lifestyle has both direct and indirect effects on financial control through self-control. Self control is the dominant variable mediating the relationship between financial literacy, lifestyle, and financial control. These findings emphasize the importance of self control in strengthening the relationship between financial literacy, lifestyle, and financial control behavior of the millennial generation. This research is expected to contribute to the development of more effective financial education strategies.